2017
DOI: 10.1038/srep42719
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of secreted Frizzled-related proteins: re-examining their proposed tumour suppressive function

Abstract: Secreted frizzled-related proteins (SFRPs), containing five family members (SFRPs 1–5) are putative extracellular Wnt inhibitors. Given their abilities to inhibit Wnt signalling, as well as the loss of SFRP1 in many cancers, this family is generally considered to be tumour suppressive. In this study we analyzed gene expression, promoter methylation and survival data from over 8000 tumour and normal samples from 29 cancers in order to map the context-specific associations of SFRPs 1–5 with patient survival, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 39 publications
(46 reference statements)
6
43
0
Order By: Relevance
“…FZD2 is elevated in many cancers, including breast cancer, and its expression correlated with markers of EMT and cell migration through a non-canonical pathway that predicts metastasis and overall survival in patients [22]. Similarly, SFRP2 is shown to be associated with poor prognosis concomitant with the expression of genes associated with EMT [47]. In agreement with the above findings, the pathway analysis of the gene expression data in this study showed enrichment of WNT (both canonical and non-canonical) pathways, the planar cell polarity (PCP) pathway, and signaling pathways regulating the pluripotency of stem cells in DCIS (generally induced by WNT signaling).…”
Section: Discussionmentioning
confidence: 98%
“…FZD2 is elevated in many cancers, including breast cancer, and its expression correlated with markers of EMT and cell migration through a non-canonical pathway that predicts metastasis and overall survival in patients [22]. Similarly, SFRP2 is shown to be associated with poor prognosis concomitant with the expression of genes associated with EMT [47]. In agreement with the above findings, the pathway analysis of the gene expression data in this study showed enrichment of WNT (both canonical and non-canonical) pathways, the planar cell polarity (PCP) pathway, and signaling pathways regulating the pluripotency of stem cells in DCIS (generally induced by WNT signaling).…”
Section: Discussionmentioning
confidence: 98%
“…The expression of SFRP1 mRNA is detectable in all tested human tissues and broad expression was observed in the endometrium [19], ovary [20], colon [21], prostate [22], and breast [17]. The Cancer Genome Atlas (TCGA) revealed reduced expression of SFRP1 various cancers including breast, colorectal, lung, bladder urothelial carcinoma, cervical squamous cell carcinoma, head and neck squamous cell carcinoma, glioblastoma multiforme, kidney renal clear cell carcinoma, stomach adenocarcinoma, and endometrium cancer compared to the normal tissues [23].…”
Section: Epigenetic Inactivation and Genomic Alterations In Sfrp1 Genementioning
confidence: 99%
“…While SFRP2 and SFRP4 were more recently reviewed [15,16], an updated review that recapitulates the association between SFRP1 and chemoresistance is limited. A pan-cancer analysis suggested that SFRPs are strongly correlated with patient survival, but there is an inconsistency between family members and cancer types [17]. A systematic review and meta-analysis of the SFRP family also revealed that SFRP1 hypermethylation was significantly associated with cancer risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a restoration of the SFRP1 expression through epigenetic drugs or the natural compound flavonoid epigallocatechin-3-gallate (EGCG), as it was shown in our recent study, could be a new therapeutic option for β-catenin mutant pediatric liver cancers (Godeke et al 2013). In contrast to other studies, the reduced SFRP1 gene expression in our HB patient cohort was not associated to the DNA methylation status (Vincent and Postovit 2017;Kaur et al 2012). Several patient samples showed a SFRP1 downregulation without a concomitant methylation of the promoter.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, it was previously shown that the dickkopf WNT signaling pathway inhibitor 1 (DKK1) is upregulated in HB patient samples, which might represent negative feedback mechanisms (Wirths et al 2003). On the contrary, among the known WNT antagonists, the secreted frizzled-related protein 1 (SFRP1) is often downregulated in various cancer entities, which indicates that SFRP1 has tumor-suppressive functions (Vincent and Postovit 2017). Under physiological conditions, SFRP1 inactivates the canonical and non-canonical WNT/β-catenin pathway by directly binding to WNT proteins or the frizzled receptor (Kawano and Kypta 2003).…”
Section: Introductionmentioning
confidence: 99%